Faktorisasi Matriks Hermitian Nonkomutatif Berdasarkan Trace - Wadu, Mira; Kumanireng, Albert Mario; Tamonob, Arista Marlince (Pendidikan Matematika FKIP Universitas Mataram, 2025)
This article studies the factorization of Hermitian matrices over a division ring based on their trace values. The main result shows that the trace determines the minimum number of Hermitian factors required in factorization depending on the trace value, namely four factors are sufficient for matrices with zero trace, while for matrices with nonzero trace, one additional diagonalizable factor is required. This result indicates a relationship between additive invariance (trace) and multiplicative invariance (Dieudonné determinant) in noncommutative linear algebra.